Novel heterozygous mutation in alpha-2-macroglobulin (A2M) suppressing the binding of amyloid-β (Aβ) - Qiu, Guozhen; Cao, Liming; Chen, Yong-Jun (Frontiers in Neurology, 2023)
Many studies have suggested that the α-2-macroglobulin (A2M) gene may be involved in the pathogenesis of Alzheimer's disease (AD). A2M encoded by the A2M gene can specifically bind to the β-amyloid peptide and prevent fiber formation. Here we describe a 65-year-old male with 5 years of gradually progressive memory loss. Based on neuropsychological tests, cranial MRI, and CSF biomarker analysis, he was diagnosed with AD. Whole-exome sequencing (WES) showed that there was a missense mutation in A2M (c.1229A>C, p.N410T). Bioinformatics analysis showed that this mutation was pathogenic. Moreover, 3D protein structure analysis showed that the A2M Asn410 residue was an N-glycosylation site, which was necessary for A2M activation to bind to Aβ. Missense mutation led to the loss of glycosylation at this site, which suppressed the binding of Aβ. The functional experiment also confirmed the prediction: the interaction between A2M and Aβ from the patient's plasma was weakened. Our results demonstrate that this novel A2M p.N410T mutation may have a pathogenic role in AD, by altering the binding interactions between A2M and Aβ.